A high throughput single-stranded conformation polymorphism assay for detection, subtyping and genotyping of influenza viruses - Quinto, Joseph D; Wang, Chiaoyin Kathy (International Congress series, 2004)
We have developed a high throughput single-stranded conformation polymorphism/capillary electrophoresis genotyping assay (SSCP/CE) to detect the presence of influenza virus and to determine its serotype, subtype and genotype. We configured the assay in two slightly different formats to suit the two applications: (i) To detect the presence of influenza virus and to determine its serotype and subtype in the clinical samples and (ii) to determine the genetic configuration of influenza virus reassortants generated by co-infection of two influenza virus strains in chicken embryo kidney (CEK) cells. We applied this newly developed assay to screen a large number of reassortants for a specific 6:2 genetic configuration characteristic of the FluMist Vaccines which exhibits two unique features: (i) the HA and NA segments from the circulating wild-type strains to confer immunogenicity and (ii) the internal segments of the master donor virus (MDV) to impart the attenuation phenotype. To evaluate the accuracy of the SSCP/CE assay, we analyzed 400 gene segments from approximately 50 different reassortant viruses and compared the SSCP/CE results with those obtained by the more conventional restriction fragment length polymorphism (RFLP) analysis. We found a very high concordance (98%) between the two sets of data.